Power system transient stability enhancement - Zhao, Jingyu (Nanyang Technological University, 2020)
Photovoltaic solar energy has been widely used in power system due to its advantages of cleanness and inexhaustibility. However, high penetration of the PV will affect the system transient stability. This report presents the detail of developing a PV generator with turbine generator for infinite bus. This report mainly focuses on using virtual synchronous generator to maintain the output when there is a fault in the load. In the report, firstly the designing of a PV power system with turbine generator will be discussed, followed with the development of a controller capable of improving transient stability. DC voltage regulator and virtual synchronous generator have been used in the controller. Lastly, the model will be test in MATLAB-Simulink environment and the result will be discussed and analyzed.